Kajian Pengaruh Penambahan Nanopartikel Perak (AgNPs) Terhadap Respon Instrumen Sensing Berbasis Surface Plasmon Resonance (SPR) - Tyas Arifani; Kamsul Abraha (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Theoretical studies have been done related to the phenomenon of surface plasmon resonance (SPR) on the system with addition of silver nanoparticles (AgNPs) that was modeled as a sensing instrument. Model is built with AgNPs placed as an additional layer over the conventional SPR system. Quantitative analysis on the model will provide a response in the form of reflectance spectrum as a function of incident angle that showed SPR angle ( SPR ) point and the attenuation. To know how the AgNPs in various sizes affect the resonance coupling, it will be calculated the dispersion relation curves obtained as the solution of Maxwell’s equations. Coupling between surface plasmon wave and evanescent wave will provide the resonance angle on the intersection of the two curves. Computational analysis of ATR method, demonstrate how the addition of AgNPs in sensing instrument configuration will improve performance of such instruments, visualized by SPR angle shift.